Literature Study on The Influence of Mathematics Basic Skills to Work Out Physics Problems - Murni Murni; Rina Mirdayanti; Burhanuddin AG (Universitas Muhammadiyah Mataram, 2018)
This research aims to describe the correlation of mathematics skills as the basic skills that students need in order to solve physics problems that seem complicated and difficult to understand. Physics describes the order of nature in mathematical equations thus the ultimate goal of physics in finding other sequences and making use of it in real life can be achieved more easily. This research was conducted using literature study approach. The data were collected by means of documentation with secondary data obtained from several references. The data were then analyzed using content analysis technique. A relevant summary of the correlation between proper mathematical understanding and complex physics problem-solving ability was attained from this research. These results were confirmed by the data gained from a range of references in the form of books, both online and offline journals as well as prior conferences that have been read, reviewed and analyzed by focusing on the mastery of mathematics skills in developing students' critical thinking to work out physics problems.